(untitled) (Materiali di Estetica. Terza serie, 2022)
The article deals with Eric Voegelin’s analysis of the symbolic dimension of politics and history. It focuses at first on the analysis of the relationship between religion, politics and totalitarianism in the essay on “political religions” and outlines some aspects of the context in which this essay was written. Some characteristics of Voegelin’s methodological reflections on the idea of a “new science” of politics are then presented and it is then shown how the attempt to understand the relationship between ideas and symbols opens a new horizon of research, in which the relationship between symbol and representation, and that between symbol, history and being, around which the monumental, and unfinished work Order and History moves, are the main axes.